Measurement and Analysis of Transmission Error of the Robot RV Reducer - Wang Haixia; Wu Qingfeng; Wu Yibo; Wang Qingzhong; Zheng Boheng; Hu Weijian (Jixie chuandong)
In order to measure the transmission error of the robot RV reducer accurately and analyze the influence of the load and input speed during the measurement process, then guide the measurement and application of the robot RV reducer, a robot RV reducer comprehensive test bench consisting of a control module, a measurement module, a software module and a mechanical module is built by selecting key test components, the transmission errors of RV-40E and RV-320E under different conditions are measured, and the transmission error curves are obtained. The relationships of transmission error between load, input speed and different models is fitted based on the experimental data, and the influence of load, input speed and stiffness on the transmission errors is analyzed. The results show that the transmission error of the robot RV reducer increases with the increase of the load and input speed, and decreases with the increase of the rigidity, and find that the influence of the load on the measured transmission error is third order, which has a greater impact.